Antibacterial Performance of a Cu-bearing Stainless Steel against Microorganisms in Tap Water. Issue 3 (March 2015) - Li, Mingjun; Nan, Li; Xu, Dake; Ren, Guogang; Yang, Ke
Abstract : Tap water is one of the most commonly used water resources in our daily life. However, the increasing water contamination and the health risk caused by pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli have attracted more attention. The mutualism of different pathogenic bacteria may diminish antibacterial effect of antibacterial agents. It was found that materials used for making pipe and tap played one of the most important roles in promoting bacterial growth. This paper is to report the performance of an innovative type 304 Cu-bearing stainless steel (304CuSS) against microbes in tap water. The investigation methodologies involved were means of heterotrophic plate count, contact angle measurements, scanning electron microscopy for observing the cell and subtract surface morphology, atomic absorption spectrometry for copper ions release study, and confocal laser scanning microscopy used for examining live/dead bacteria on normal 304 stainless steel and 304CuSS. It was found that the surface free energy varied after being immersed in tap water with polar component and Cu ions release. The results showed 304CuSS could effectively kill most of the planktonic bacteria (max 95.9% antibacterial rate), and consequently inhibit bacterial biofilms formation on the surface, contributing to the reduction of pathogenic risk to the surrounding environments.